Transnational religious spaces : faith and the Brazilian migration experience - Sheringham, Olivia (Migration, diasporas and citizenship., 2013)
This book explores the role of religion in the everyday, transnational lives of Brazilian migrants in London and on their return to Brazil. It contributes to an emerging body of work that recognizes the importance of religion within transnational processes and foregrounds the experiences of Brazilians in London, a growing yet still largely invisible new migrant group in London. It works with the notion of religion as lived experience to give due weight to the perspectives of migrants themselves and examines the ways in which migrants negotiate their religious beliefs and practices in different places and create new connections between them. While focusing on the experience of Brazilian migrants - both in London and on their return - as a case study, it provides significant empirical and conceptual contributions to existing research through its innovative exploration of the interconnections between migration and religion, and moreover, through its inclusion of the return setting into its field of enquiry. Both these areas ₆ religion and return ₆ have been hitherto largely neglected within existing migration research.